One-half of Marvin’s age two years from now plus one-third of his age three years ago is twenty years. How old is Marvin now?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Then we have:
2 x + 2 + 3 x − 3 2 x + 1 + 3 x − 1 6 3 x + 2 x 5 x ⟹ x = 2 0 = 2 0 = 2 0 = 1 2 0 = 5 1 2 0 = 2 4
Marvin's age is 2 1 + 3 1 2 0 = 2 4 years. Correct? :)
Generalization :
The sum of ( x 1 )'th of someone's age x years from now and ( y 1 )'th of his age y years ago is x y 3 7 ( x + y ) years. How old is he now?
Let M = present age of Marvin
M + 2 = Marvin’s age two years from now
M – 3 = Marvin’s age three years ago
(1/2)(M + 2) + (1/3)(M - 3) = 20
M/2 + 1 + M/3 – 1 = 20
M/2 + M/3 = 20
6(M/2 + M/3 = 20)
3M + 2M = 120
5M = 120
M = 24
Problem Loading...
Note Loading...
Set Loading...
Let the following be true:
x = Marvin’s current age
y = Marvin’s age 3 years ago
z = Marvin’s age 2 years from now
If that's true, we're solving for x , so:
x = x
y = x − 3
z = x + 2
So, according to the problem, here's our equation:
2 1 z + 3 1 y = 2 0
Once the above equation is simplified, we have:
3 z + 2 y = 1 2 0
Once we put both z and y in terms of x , our equation becomes:
3 ( x + 2 ) + 2 ( x − 3 ) = 1 2 0
Which becomes:
3 x + 6 + 2 x − 6 = 1 2 0
Simplifying the above equation gives:
5 x = 1 2 0
Therefore, x = 2 4 , meaning the answer is that Marvin's current age is 24.